2020
DOI: 10.1002/brb3.1879
|View full text |Cite
|
Sign up to set email alerts
|

Identifying functionally relevant candidate genes for inflexible ethanol intake in mice and humans using a guilt‐by‐association approach

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In this context, our research group identified relations of the Lrrk2 gene, until then associated with Parkinson’s and inflammatory bowel diseases, in preference behavior and loss of control by alcohol in mice, Zebrafish, and humans ( 31 , 32 , 36 , 108 110 ). This gene is involved in neural processes, such as the reuptake of synaptic components and synaptic plasticity, and in several signaling pathways by performing GTPase and kinase functions, which influence processes such as cell proliferation and differentiation, apoptosis, inflammation, and immune response ( 50 , 111 116 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, our research group identified relations of the Lrrk2 gene, until then associated with Parkinson’s and inflammatory bowel diseases, in preference behavior and loss of control by alcohol in mice, Zebrafish, and humans ( 31 , 32 , 36 , 108 110 ). This gene is involved in neural processes, such as the reuptake of synaptic components and synaptic plasticity, and in several signaling pathways by performing GTPase and kinase functions, which influence processes such as cell proliferation and differentiation, apoptosis, inflammation, and immune response ( 50 , 111 116 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the inflammatory process is observed in the striatum, changing its function and stimulating the drug compulsive use, even in the presence of negative consequences (16). Changes in the striatum are associated with compulsion as this brain region plays a central role in goal-directed behaviors and it is part of the Mesolimbic Dopaminergic System, popularly known as the reward system (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…The QTL enrichment analysis was performed using GALLO as described by Fonseca et al (2020a). A guilt-by-association approach was performed to identify potential functional candidate genes (Fonseca et al, 2020b;Martins de Carvalho et al, 2020;Sweett et al, 2020;Lam et al, 2021). Briefly, a trained list containing genes associated with stillbirth and pregnancy persistence was obtained from GUILDify (Guney et al, 2014), using the following list of keywords: stillbirth, pregnancy, and pregnancy loss.…”
Section: Functional Candidate Genes Searchmentioning
confidence: 99%
“…Mutations in the human LRRK2 gene are associated with Parkinson’s disease [ 8 , 9 ], which is characterized by prominent impairment in dopamine signaling and basal ganglia function. Recent work has linked changes in striatal expression of the Lrrk2 gene with alcohol drinking in humans and rodents [ 10 , 11 ]. A positive correlation between striatal levels of Lrrk2 mRNA and alcohol drinking was reported in mice, especially an association with inflexible alcohol drinking that persists despite adverse outcomes or punishment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%